(untitled) (Bangladesh Pharmaceutical Journal, 2018)
Disaccharides, such as sucrose, have been reported to protect phospholipid membranes during drying, while HPMC is used as gel matrix to inhibit recrystallization. We have investigated the solid state characterization of dried liposome formulation (air-dried and freeze-dried) which was preserved in the presence of sucrose and dispersed in HPMC matrix. The dried liposomal featured cationic dimethyldioctadecylammonium (DDA) was produced to overcome detrimental phase separation in phospholipid membranes during manufacturing process. The effect of sucrose and HPMC on lipid phase behavior during dehydration were characterized including their thermodynamics by DSC, crystallinity by XRD, and liposome structure by SEM. Data revealed that formula contain 5% sucrose and 7.5% HPMC showed a miscible mixture and relatively less crystalline-forming properties that potentially construct a stable dried liposome. The results may aid in the development of dried–DDA liposomal formulation by using combination of sucrose and HPMC. Bangladesh Pharmaceutical Journal 21(1): 16-23, 2018